PENGARUH IMPLEMENTASI PROGRAM 5S UNTUK MENINGKATKAN PRODUKTIVITAS DI UMKM JBMS FOOD KABUPATEN PESAWARAN - Putri Endah Suwarni (Industrika : Jurnal Ilmiah Teknik Industri, 2019)
The JBMS Food is one of the micro, small and medium enterprises engaged in the processing of various snacks. Behavior of workers or employees at UMKM (Usaha Mikro Kecil dan Menengah) still lacks support in progress. Where the work culture of employees who cannot return and rearrange the equipment that has been used in accordance with their original existence makes one of the inhibiting factors in the smooth work. The method used is to use the basic approach of the 5S concept (Seiri, Seiton, Seiso, Seiketsu, and Shitsuke). This research aims to improve a better work environment as an effort to increase productivity through the implementation of the 5S program. The evaluation value of the 5S program in the production area at the JBMS FOOD before the application of the 5S program has attainment of 42.5%, while the evaluation value of the 5S program after improvement is 82.5%. Before implementing 5S, the workforce was able to produce 10 kg / 120 minutes of chips, while 5S was implemented and the work method was improved, it proved that the workforce was able to produce 12 kg / 120 minutes of chips. So that there is an increase in productivity of 20% from before 5S implementation. Keywords: Implementation, 5S, Productivity, UMKM